Transformasi Budaya Organisasi pada Perguruan Tinggi Keagamaan Islam Negeri - Fauzi, Farid (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
The dynamics of cultural change is something that happens today. State Islamic College (PTKIN). The challenge against cultural change at PTKIN is a phenomenon that occurs in the development and changes in PTKIN’s internal and external environment. The transformation of organizational culture at PTKIN will require changes in organizational performance. PTKIN’s organizational culture changes emphasize the principle of adiptif, agreement and interest in the needs and desires of stakeholders, technological developments and information and in accordance with the strategic plan of PTKIN.